Carbon sequestration potential and soil characteristics of various land use systems in arid region. (15th June 2020) - Hammad, Hafiz Mohkum; Fasihuddin Nauman, Hafiz Muhammad; Abbas, Farhat; Ahmad, Ashfaq; Bakhat, Hafiz Faiq; Saeed, Shafqat; Shah, Ghulam Mustafa; Ahmad, Amjad; Cerdà, Artemi
Abstract: Soils contain one of the largest carbon (C) pools in the biosphere with the greatest potential of C sequestration to mitigate climate change impacts. The present study aimed at comparing C sequestration potential of various land use systems including forestlands, croplands, agroforests, and orchards in the arid region of Pakistan. Soil samples from the layers of 0–20, 20–40, 40–60, and 60–80 cm depths were collected and analysed for soil physico-chemical properties namely texture, pH, EC, NPK-soil, organic matter (SOM), and soil organic C (SOC). Additionally, the above and below ground plant biomass and C contents were estimated. Results revealed that the highest C sequestration potential (64.54 Mg ha −1 ) was in the above ground biomass of forest land and the lowest (33.50 Mg ha −1 ) in cropland. The below ground plant biomass at 0–20 cm soil depth was 14.09, 12.38, 11.78, 11.76, and 10.92 Mg ha −1 for forest land, mango orchards, agroforests, citrus orchards and cropland, respectively. The respective values in case of total C content were, 6.84, 6.79, 6.10, 5.69 Mg ha −1 . Irrespective to the soil depth, below ground biomass and total C followed the order: forest land > mango orchard > citrus orchard > agroforests > crop lands. It is concluded that the forest land have greater potential for C sequestration than the other land use systems studied in the arid region of Pakistan. Therefore, in order to cope up with climate change disasters in Pakistan the massive reforestation project – named the Billion Tree Tsunami of the Government of Pakistan will prove beneficial. Graphical abstract: Image 1098 Highlights: Anthropogenic activities instigate carbon footprints. Agriculture land use systems serve to mitigate greenhouse gases emissions. It is necessary to reconsider agricultural land use systems for calculating global carbon footprints.